Comparing ICD-10 external cause codes for pedal cyclists with self-reported crash details. Issue 2 (16th February 2017) - Beck, Ben; Ekegren, Christina L; Cameron, Peter; Stevenson, Mark; Judson, Rodney; Bucknill, Andrew; Edwards, Elton; Gabbe, Belinda
Abstract : Accurate coding of injury event information is critical in developing targeted injury prevention strategies. However, little is known about the validity of the most universally used coding system, the International Classification of Diseases (ICD-10), in characterising crash counterparts in pedal cycling events. This study aimed to determine the agreement between hospital-coded ICD-10-AM (Australian modification) external cause codes with self-reported crash characteristics in a sample of pedal cyclists admitted to hospital following bicycle crashes. Interview responses from 141 injured cyclists were mapped to a single ICD-10-AM external cause code for comparison with ICD-10-AM external cause codes from hospital administrative data. The percentage of agreement was 77.3% with a κ value of 0.68 (95% CI 0.61 to 0.77), indicating substantial agreement. Nevertheless, studies reliant on ICD-10 codes from administrative data should consider the 23% level of disagreement when characterising crash counterparts in cycling crashes.